Avances del diagnostico de frijol en la zona de Los Altos de Jalisco, Mexico - Chavez C., J.R.; Flores L., H.E.; Aleman M., V.; Mier C., R.; Aceves R., J. de J.; Ledesma G., L.A.; Plascencia M., J.; Lépiz Ildefonso, Rogelio (International Center for Tropical Agriculture, 1987)
A survey of the farmers in the semi-arid and humid areas of Los Altos de Jalisco, Mexico, was conducted to determine the constraints on bean yield in the area. Based on the information collected, the most important characteristics of the production systems of beans in monoculture and association are described, including planting, fertilization, harvest, area planted, land tenancy, and weed and pest control. (CIAT)